Boron-Doped Edges as Active Sites for Water Adsorption in Activated Carbons - Wee, Jae-Hyung; Kim, Chang Hyo; Tojo, Tomohiro; Choi, Go Bong; Yang, Cheol-Min; Kim, Yoong Ahm (AMER CHEMICAL SOC, 2021)
Investigating the surface properties of heteroatom-doped carbon materials is essential because these versatile materials have found use in a variety of energy and environmental applications; an understanding of these properties would also lead to an improved appreciation of the direct interaction between the reactant and the functionalized surface. Herein, we explore the effect of boron (B) doping on the surface properties of activated carbon (AC) materials based on their water adsorption behavior and oxygen reduction reaction. In the high-temperature B doping process, B-doped AC materials at 1400 degrees C exhibit an open pore structure with B-O bonds, whereas at a temperature of 1600 degrees C, a nonporous structure containing a large amount of B-C bonds prevails. The B-O species act as active sites for water adsorption on the carbon surface. On the basis of the isothermal adsorption heat, we suggest that B atoms are present at the pore openings and on the surfaces. The B-O moieties at the open edges improve the electrocatalytic activity, whereas the B-C bonds at the closed edges decrease the electrocatalytic activity because of the stable structure of these bonds. Our findings provide new evidence for the electrocatalytic properties associated with the structure of B-doped edges.
Keywords: OXYGEN REDUCTION REACTION; SURFACE-CHEMISTRY; MICROPOROUS CARBON; HEAT-TREATMENT; PORE-SIZE; CATALYSTS; GRAPHENE; RAMAN; NANOTUBES; EVOLUTION